When should you suspect if your patient is an Anabolic-Androgenic Steroid User? Evidence-Based literature review of usage patterns changes and clinical implications for medical practice (2005-2025) - Pielech, Adrianna; Dadyńska, Patrycja; Wilczyński, Marek; Kwiecień, Paweł; Kwiecień, Michał; Zielska, Julianna (Journal of Education, Health and Sport, 2026)
Background: Anabolic-androgenic steroid (AAS) use has evolved into a significant public health concern affecting diverse populations beyond elite athletics. Objective: To examine evidence-based changes in AAS usage patterns including demographics, motivations, and health consequences from 2005-2025 using systematic reviews and peer-reviewed research. Methods: Literature review of peer-reviewed studies and systematic reviews from PubMed and National Health Institute Library focusing on AAS epidemiology, demographic changes, and health consequences published between 2005-2025. Results: Global lifetime prevalence of AAS use is estimated at 6-29%. Female participation is estimated to be constantly growing. Evidence indicates expansion beyond traditional athletic populations with significant cardiovascular, psychiatric, and reproductive health consequences. Conclusions: AAS use represents a widespread public health concern requiring enhanced clinical awareness and evidence-based management approaches among medical practitioners.